Supporting institution-to-community transitions for people with psychiatric disabilities: Findings and implications from a participatory action research project - Zakrajsek, Andrea Gossett; Mirza, Mansha; Chan, Nathan Kai-Cheong; Wilson, Tom; Karner, Mark; Hammel, Joy (Disability Studies Quarterly, 2014)
Despite preference for community-based living, large numbers of people with psychiatric disabilities live in nursing homes throughout the US. Community-based services for this population are limited by public policy and service system barriers. This paper summarizes these barriers and presents the second phase of a participatory action research project jointly developed by university-based researchers and two Centers for Independent Living. A qualitative case study methodology was used to understand the experiences of three individuals with psychiatric disabilities reintegrating into the community from nursing homes. Findings revealed themes of social isolation, participation in virtual communities, variability of impairment experiences and unmet needs for community supports. In addition to thematic findings, action products were generated for the benefit of community partners. These products included national best practice resources and a needs assessment survey tool. Study findings and products point to specific systems change and policy recommendations to better support community reintegration for this population. These recommendations are discussed in light of U.S. healthcare reform and broader disability advocacy efforts.